Explanatory pluralism in economics: Against the mainstream? - Van Bouwel, Jeroen (Philosophical Explorations, 2004)
Recent pleas for more heterodoxy in explaining economic action have been defending a pluralism for economics. In this article, I analyse these defences by scrutinizing the pluralistic qualities in the work of one of the major voices of heterodoxy, Tony Lawson. This scrutiny will focus on Lawson's alternatives concerning ontology and explanation to mainstream economics. Subsequently, I will raise some doubts about Lawson's pluralism, and identify questions that will have to be addressed by heterodox economists in order to maintain the claim of pluralism.